PERTIMBANGAN PUTUSAN HAKIM PERKARA HARTA BERSAMA NO.0233/PDT.G/2018/PA.TBH DI PENGADILAN AGAMA TEMBILAHAN - Azmil Fauzi Fariska (Al-Maslahah : Jurnal Ilmu Syariah, 2021)
This research is motivated by the decision of the panel of judges at the Tembilahan Religious Court which decided the joint property case, the judge decided that the Plaintiff (husband) got 1/4 while the Defendant (wife) got 3/4 of the joint property, which the judge's decision is not in accordance with the KHI article 97. The results of the decision research are in accordance with the judge in deciding the case based on Legal Certainty (legal certainty) and Legal Justice (legal justice), legal certainty is what has been outlined by legislation, the Compilation of Islamic Law, such as this case according to legal certainty then the distribution is that the wife gets 1/2 and the husband gets 1/2 so if only this is applied rigidly in the case it will reduce the values of justice itself, thus the judge in determining this joint property case uses Legal Justice. Law). In Islam the concept of justice is to put something in its place, to give something that is rightfully his with a balanced level. During the marriage the Defendant (wife) was more dominant in earning a living and producing property, which then became the source for buying and renovating the house which is currently the object of dispute.